PENGUATAN PERAN PEMERINTAH DESA, PEMUDA, DAN MASYARAKAT DALAM PELESTARIAN BUDAYA LOKAL DI DESA LUBUK BATANG LAMA KABUPATEN OGAN KOMERING ULU - Andika Wijaya Sairi; Vrischa Oktaviyana Rini; Yahnu Wiguno Sanyoto; Marratu Fahri Marratu; Farah Nisrina Zalfa Farah; Eriyansyah Erik (STKIP Subang, 2026)
The preservation of local culture is an important effort to maintain the identity and social values of the community amid the rapid development of globalization. A socialization activity themed “Strengthening the Role of Village Government, Youth, and Community in Preserving Local Culture” was carried out as part of the Village Government Course Practicum in the Government Science Study Program at Baturaja University. This activity aims to increase community understanding of the importance of synergy between village government, youth, and the community in preserving and developing local culture. The methods used included a pre-test, material presentation, interactive discussion, Q&A, and a post-test. The activity was held on June 15, 2026, in Hamlet 8 of Lubuk Batang Lama Village, Lubuk Batang District, Ogan Komering Ulu Regency, involving 30 participants consisting of village government, hamlet officials, community members, and village youth. The results of the activity showed an increase in participants’ understanding from an average of 64.2% on the pre-test to 90.4% on the post-test. In addition, the activity successfully raised community awareness about the importance of documenting village history, preserving local culture, and the need for collaboration between village governments, youth, and the community in maintaining regional cultural heritage.